Religious Studies in the Islamic World: Revisiting the Muslim Challenge to Religious Studies Discourse - Arnanda, Yarsa (Aqlania, 2024)
The challenges and responses given by Muslims, especially Muslim scholars to Religious Studies are the starting point of this research. Departing from these problems, the author aims to answer the questions of why Islam challenges Religious Studies, how Muslims challenge or respond to Religious Studies, and how to solve these problems. Muslim opposition to Religious Studies is the author's entry point to revisit this discipline. The problematic legacy of Orientalism conducted by Western scholars is one of the factors of Muslim rejection of Religious Studies. It is also what makes Muslims suspicious of anything that comes from the West. By revealing Muslim opposition to Religious Studies, the author reflects on this opposition as an effort to resist the discourse of Religious Studies which seeks to separate the religious world and the secular world as mentioned by Timothy Fitzgerald. Furthermore, Muslim criticism of Religious Studies is used as a social reality to reassess Religious Studies. The author tries to bring Religious Studies, especially the field of Islamic Studies, into the epistemological framework of Islam itself. Finally, with regard to modernity, the author considers various methodologies or approaches that have developed in the Western world to be used as an analytical knife to study Islam in its various aspects in the realm of Religious Studies research. In this case the author wants to emphasize that not everything that comes from the West is something negative that can damage the image of Islam.